Furuncular myiasis in Italian traveler returning from Kenya - Ester Oliva; Graziano Bargiggia; Gianpaolo Quinzan; Paola Lanza; Claudio Farina (Journal of Infection in Developing Countries)
Myiasis has been defined as the infestation of organs and/or tissues with dipterous larvae. They are especially widespread in tropical and subtropical areas. Cutaneous myiasis is its most frequent clinical presentation. This report presents a case of furuncular myiasis caused by the larva of Cordylobia anthropophaga in a 22-year-old girl living in Bergamo, Northern Italy, who returned from Kenya (Watamu) with a big, painful furuncle in her right gluteus. The patient accidentally removed the larva from a large pimple and took it to the infectious disease ambulatory clinic at the ASST “Papa Giovanni XXIII” Hospital, Bergamo. In the Microbiology and Virology Department of the same hospital, a larva of C. anthropophaga was identified and the diagnosis of myiasis was confirmed.